Pharmacologic treatments for esophageal disorders. (29th September 2014) - Blackshaw, L. Ashley; Bordin, Dmitry S.; Brock, Christina; Brokjaer, Anne; Drewes, Asbjørn Mohr; Farmer, Adam D.; Krarup, Anne Lund; Lottrup, Christian; Masharova, Antonina A.; Moawad, Fouad J.; Olesen, Anne Estrup
Abstract : The following, from the 12th OESO World Conference: Cancers of the Esophagus, includes commentaries on the role for ketamine and other alternative treatments in esophageal disorders; the use of linaclotide in the treatment of esophageal pain; the alginate test as a diagnostic criterion in gastroesophageal reflux disease (GERD); the use of baclofen in treatment of GERD; the effects of opioids on the esophagus; the use of antagonists on the receptor level in GERD; the effect of local formulation of drugs on the esophageal mucosa; and the use of electroencephalographic fingerprints to predict the effect of pharmacological treatment.